Pengaruh Kondisi Keuangan dan Makroekonomi Terhadap Kemungkinan Financial Distress - Rizki Indah Lestari; Triyono (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the effect of projected financial and macroeconomic ratios with liquidity, solvency, profitability, activity, economic growth, and interest rate ratios on the possibility of financial distress in manufacturing companies in the property and real estate sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. This type of research is quantitative using secondary data obtained from the financial statements of property and real estate sector companies for 2020-2023 obtained from the website www.idx.co.id. The sampling method used purposive sampling with a selected sample size of 267 from 70 companies from 2020-2023. This study uses logistic regression analysis to test whether the probability of the dependent variable can be predicted by the independent variable. The results of this study indicate that the liquidity, profitability, and activity ratios have a significant negative effect on the possibility of financial distress. Meanwhile, the solvency ratio and interest rate do not have a significant effect on the possibility of financial distress with a positive direction. The economic growth variable also shows results that do not have a significant negative effect on the possibility of financial distress.